PENUMBUHAN JIWA KEWIRAUSAHAAN MELALUI PRAKTIK BISNIS DI BUSINESS CENTER ( STUDI KASUS: SMK MUHAMMADIYAH 2 SURAKARTA) - Tri Kuat (Jurnal Pendidikan Ilmu Sosial, 2015)
Education has very strategic role to reach up the progressing of one nation,also as basic capital and human investment. The research aims is to knowhow business practice that is conducted at SMK Muhammadiyah 2Surakarta. And, whether business practice is able to grow up the spirit ofentrepreneurship. The research target is students of SMK Muhammadiyah 2Surakarta: 326 students, principal, teachers, and staffs. The research kinds is qualitative.Collecting data through observation, in depth interview, and documentation. Dataanalysis through qualitative descriptive by using triangulation model. The research resultshow that business practice conducting at SMK Muhammadiyah 2 Surakarta can beconducted successfully and able to grow up the spirit of entrepreneurship.